A new assessment of the Troika´s economic policy for Portugal in 2012 following an Input-Output approach - Coelho, José Carlos (2020)
This article proposes a new evaluation of the economic and financial adjustment programme negotiated between Portugal and the Troika (European Commission, European Central Bank and International Monetary Fund) for the year 2012, in an Input-Output framework. As in Amaral and Lopes (2017), a comparison is made between the unemployment rate forecast for 2012 and that which would result from obtaining the implicit target for the external deficit, concluding that the unemployment rate was underestimated by almost two percentage points. We also concluded that the achievement of the implicit target for the external deficit in 2012 would only be compatible with the establishment of a lower budget deficit and a lower of weight of budget deficit on GDP for that year. Such an objective would require a smaller amount of transfers made by the Government to households and would result in greater contractions in private consumption and GDP and would result in a higher unemployment rate than that expected by the Troika for 2012.